ANALYSIS THE EFFECT USER READINESS ON ACCEPTANCE OF PEDULILINDUNGI APPLICATIONS USING METHOD TECHNOLOGY READINESS ACCEPTANCE MODEL (TRAM) BASED ON THE PERSPECTIVE OF GENERATION Z USERS - Sulton Ainun Nazib; Windi Eka Yulia Retnani; Beny Prasetyo (JUTI: Jurnal Ilmiah Teknologi Informasi, 2023)
The PeduliLindung application is a new application released on March 28, 2020 by the Ministry of Communications and Informatics to be used to track and collect data to stop the spread of the Covid-19 virus in Indonesia. Judging from the Google Play Store, the PeduliLindung application received a rating of 3.6 as of October 2021 and received many negative responses from users. Therefore, to measure the success of the adoption of the PeduliLindung application, an evaluation of the level of readiness and acceptance of PeduliLindung application users will be carried out. This study aims to analyze the effect of user readiness on acceptance of the PeduliLindung application using the Technology Readiness Acceptance Model (TRAM) method based on the perspective of generation Z users. This study involved 349 generation Z respondents who were users of the PeduliLindung application and had vaccinated at least dose 1 as a sample of the population of application users. CareProtect. The data obtained will be analyzed using SmartPLS. The results of this study indicate that the level of readiness of users of the PeduliLindung application based on the perspective of generation Z users is in the high readiness category, and 4 of the 10 proposed hypotheses are accepted, and the remaining 6 are rejected hypotheses.